The third anniversary of William Harvey - Lastres, Juan B. (1958)
The civilized world commemorated in 1957, the third anniversary of the death of William Harvey, English illustrious genius like Linacre, Sydenham, Oster, Lister, Fleming and many others defined road map drawn to science, and inaugurated new exploration methods which has benefited mankind.